A metaphor analysis of older adults' lived experience of household isolation during COVID-19 - Wilding, Ell; Bartl, Sara; Littlemore, Jeannette; Clark, Maria; Brooke, Joanne (Frontiers in Communication, 2023)
In March 2020, Public Health England provided social distancing and shielding guidance for all adults aged 70 and over in response to the COVID-19 pandemic. This article analyses the metaphors used by 13 older adults when discussing their experiences of household isolation to provide insight into their lived experiences of household isolation, particularly in relation to a loss of agency. We found that participants negotiated their sense of agency through the use of metaphors involving physical force, movement, space, and animation of COVID-19. Metaphors were particularly used to discuss negative emotional impacts of the pandemic. Perceptions of a loss of agency were sometimes redressed through the use of comforting metaphors involving patterns and structure. In addition, participants explicitly rejected or refashioned dominant public metaphors that circulated as part of Government campaigns and wider public discourse to describe the pandemic and encourage certain behaviours. It has been argued that commonly used metaphors relating to containment, e.g. ‘bubble’, when applied to the context of household isolation, foreground the actions of those outside the container rather than those inside it, leading to a loss of feelings of agency. The participants’ reactions to these suggest that common metaphors in public discourses are appropriated selectively and are often challenged by those at whom they are targeted. Hence, metaphor analysis can be used to paint a rich picture of the lived experience of older people experiencing household isolation, including their reaction to dominant public metaphors.